2017
DOI: 10.1103/physrevb.95.214413
|View full text |Cite
|
Sign up to set email alerts
|

Spin pumping, dissipation, and direct and alternating inverse spin Hall effects in magnetic-insulator/normal-metal bilayers

Abstract: We theoretically consider the spin-wave mode-and wavelength-dependent enhancement of the Gilbert damping in magnetic insulator-normal metal bilayers due to spin pumping as well as the enhancement's relation to direct and alternating inverse spin Hall voltages in the normal metal. In the long-wavelength limit, including long-range dipole interactions, the ratio of the enhancement for transverse volume modes to that of the macrospin mode is equal to two. With an out-of-plane magnetization, this ratio decreases w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 45 publications
0
4
0
2
Order By: Relevance
“…The first experiments tried to exploit the parametric pumping of the FMR mode to move it to higher frequencies [28]. However, as pointed out by Weiler et al, not only does inductive coupling to the microwave field lead to spurious AC contributions, but the precessing motion of the magnetization in the MOI itself also inductively couples AC voltages [28,31,32,35,40]. Despite these issues, it has been shown that this AC component is considerably larger than the DC part of spin pumping, making it relevant for future applications [40,198].…”
Section: Electrically Detected Spin Pumpingmentioning
confidence: 99%
See 1 more Smart Citation
“…The first experiments tried to exploit the parametric pumping of the FMR mode to move it to higher frequencies [28]. However, as pointed out by Weiler et al, not only does inductive coupling to the microwave field lead to spurious AC contributions, but the precessing motion of the magnetization in the MOI itself also inductively couples AC voltages [28,31,32,35,40]. Despite these issues, it has been shown that this AC component is considerably larger than the DC part of spin pumping, making it relevant for future applications [40,198].…”
Section: Electrically Detected Spin Pumpingmentioning
confidence: 99%
“…An important result of these experiments is that the interface of the MOI/NM heterostructures is as transparent as all metallic ferromagnet/NM structures, showing that pure spin current transport across the interface can be very efficient in MOI/NM systems [22]. In the early stages, spin pumping experiments mostly dealt with the time-invariant part of the injected spin current in the NM, while quite recently the time-varying part of the pure spin current has been brought into focus, as it may pave the way to high processing speeds in the THz regime [28][29][30][31][32][33][34][35][36][37][38][39][40][41][42]. Moreover, the reciprocal effect of spin pumping enables us to drive magnetization dynamics and spin waves by applying a DC charge current bias to MOI/NM systems [43][44][45][46].…”
Section: Introductionmentioning
confidence: 99%
“…Второй механизм обусловлен обменным взаимодействием на интерфейсе и применительно к бегущим МСВ в структурах ЖИГ/Pt рассматривался в работах [54,55]. При этом влияние спиновой накачки на распространение ПМСВ учитывалось через граничные условия на закрепление поверхностных спинов на границе ЖИГ/Pt и проявлялось в росте потерь ПМСВ.…”
Section: влияние электронов проводимости на дисперсию и затухание пмс...unclassified
“…При этом влияние спиновой накачки на распространение ПМСВ учитывалось через граничные условия на закрепление поверхностных спинов на границе ЖИГ/Pt и проявлялось в росте потерь ПМСВ. Было показано, что в структурах на основе пленок ЖИГ с магнитной поверхностной анизотропией, характеризуемой константой 𝐾 𝑠 , связанный со спиновой накачкой параметр релаксации ∆α не зависит от толщины 𝑑 пленки ЖИГ, если выполняется условие [55]: Кривая 3 на рис. 2, a отвечает расчету зависимости 𝑘(𝑓 ) с помощью дисперсионного уравнения для ПМСВ [21]:…”
Section: влияние электронов проводимости на дисперсию и затухание пмс...unclassified
“…Spin currents in Y 3 Fe 5 O 12 /Platinum (YIG/Pt) bilayers have attracted much attention in the past decade due to the unique spin current transport properties in magnetic insulators and spin charge conversion in heavy metals [1][2][3][4][5][6][7][8][9][10][11][12][13][14]. Mechanisms including spin pumping at the bilayer interface [15], spin diffusion [16] and the inverse spin Hall effect in heavy metals [17], have been established to interpret the generation, transfer and conversion of spin current [18].…”
Section: Introductionmentioning
confidence: 99%